PLACENTA ACCRETA SPECTRUM DISORDERS - SHELLY KHILLAN; PARNEET KAUR; BEANT SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Placenta accreta spectrum is a rare pathology, but there is an increase in the incidence of placenta accreta. In the accreta spectrum, abnormal placental adherence to the myometrium stems in part from partial or total absence of the decidua basalis and imperfect development of the fibrinoid or Nitabuch layer. This results in the absence of a physiological line of cleavage, so resulting in failure of separation of the placenta causing significant hemorrhage. This leads to maternal morbidity and mortality. 12 patients of placenta accreta managed at Government Medical College and Rajindra Hospital, Patiala, over 1 year (December 2021–November 2022) were reported. All cases had a histopathologically proven diagnosis of placenta accreta. The major risk factors identified were placenta previa, previous cesarean section, multiparity, advanced maternal age, previous uterine surgeries, or curettage. Ultrasound (USG) color Doppler and magnetic resonance imaging allowed us to strongly suspect the presence of placenta accreta in a pregnant woman with risk factors. Placenta accreta spectrum is associated with life-threatening hemorrhage, urinary bladder injury, intensive care unit admission, massive blood transfusion, and maternal death. The course of action in each and every patient varies according to whether the diagnosis of the placenta is made antenatal or during C-section and the amount of blood loss.